2022
DOI: 10.1186/s12868-022-00748-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol efflux regulator ABCA1 exerts protective role against high shear stress-induced injury of HBMECs via regulating PI3K/Akt/eNOS signaling

Abstract: Background In brain, microvascular endothelial cells are exposed to various forces, including shear stress (SS). However, little is known about the effects of high shear stress (HSS) on human brain microvascular endothelial cells (HBMECs) and the underlying mechanism. The cholesterol efflux regulator ATP-binding cassette subfamily A member 1 (ABCA1) has been demonstrated to exert protective effect on HBMECs. However, whether ABCA1 is involved in the mechanism underneath the effect of HSS on HBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…It has been reported that VEGFA affects the development of AS by regulating lipid metabolism [ 30 ] and endothelial function [ 31 ]. Moreover, CTNNB1, MMP9, and EGFR have been shown to regulate AS by affecting the formation and stability of plaques through antioxidation and apoptosis inhibition [ 32 , 33 ]. Molecular docking is an important technique for discovering new medicines and improving existing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that VEGFA affects the development of AS by regulating lipid metabolism [ 30 ] and endothelial function [ 31 ]. Moreover, CTNNB1, MMP9, and EGFR have been shown to regulate AS by affecting the formation and stability of plaques through antioxidation and apoptosis inhibition [ 32 , 33 ]. Molecular docking is an important technique for discovering new medicines and improving existing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The efficient energy storage technology, which requires several kinds of critical metals, is expected to well solve the problem caused by photovoltaic power generation and wind power generation characterized by strong intermittency and high volatility. Lithiumion batteries with low cost, high efficiency, and fast response time are ahead of other energy storage technologies (Li et al, 2022). Future energy storage technologies will focus on the development of lithiumion batteries.…”
Section: Introductionmentioning
confidence: 99%